Induction of amyloid-β(1-42) in the retina and optic nerve head of chronic ocular hypertensive monkeys - Ito, Yasushi (Molecular Vision, 2012)
PURPOSE: Recent studies have indicated that accumulation of amyloid β(1–42) (Aβ(1–42)), which is associated with the progression of Alzheimer disease, may also be responsible for retinal ganglion cell death in glaucoma. The purpose of this study was to investigate the expression and localization of Aβ(1–42) in the retina and the optic nerve head (ONH) of monkeys with experimental glaucoma. METHODS: Five cynomolgus monkeys with a glaucomatous left eye at 4, 9, 11, 15, and 24 weeks after laser photocoagulation treatment were studied by immunohistochemical methods. Another two cynomolgus monkeys with a glaucomatous left eye at 133 weeks after laser photocoagulation treatment were used to measure Aβ(1–42) concentrations in the retina by enzyme-linked immunosorbent assay. RESULTS: At 11 to 24 weeks after the laser photocoagulation treatment, Aβ(1–42) was upregulated in the nerve fiber layer (NFL) and the ganglion cell layer (GCL) of the retina and the ONH, but the expression of amyloid precursor protein decreased in the NFL and ONH from levels at 9 weeks. The localizations of Aβ(1–42) were merged in glial fibrillary acidic protein-positive astroglial cells but not phosphorylated neurofilament heavy- or nonphosphorylated neurofilament heavy-positive axons in the retina and the ONH. Likewise, Aβ(1–42) concentrations in the retina of monkeys increased in the chronic stage of glaucoma. CONCLUSIONS: These findings indicate that the upregulation of Aβ(1–42) after an intraocular pressure elevation could apply to monkeys since the structure of the ONH is more similar to humans than that of rodents.